School-based enterprise and school –to – work transitions in fashion and textiles vocations: a conceptual model for HND CBT Fashion and Textiles Programme in Ghanaian Polytechnics - Crentsil, Timothy (2016)
A dissertation submitted to the Department of General Art Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Art Education.